Morphostructural aspects of the sandstone karst in Northeastern Brazil: Example from Serra da Capivara – PI - Silva, Mickaelle Braga da; Maia, Rubson Pinheiro (Revista Brasileira de Geomorfologia, 2024)
This work analyses morphostructural aspects and their influence on the development of the karst relief of Serra da Capivara (State of Piauí, northeastern Brazil). For this purpose, structural data derived from lineament extraction, sedimentary bed geometry, karstification degree of the layer, and analysis of the karst morphology were performed. Structural lineament data showed a NE-SW orientation trend, coinciding with the orientation of the Transbrasiliano Lineament. The reactivation of the brittle structures can be related to the orientation, scarp retreat, direction, and incision of the main valleys. From the analysis of the fracture array (NE-SW) and bedding planes, we suggest that the fracture connectivity of these structures resulted in conduit formation, which evolved to form subterranean galleries. Thus, the expansion of the karst system led to the formation of valleys, which are situated in higher deformed zones, such as fold hinges. These valleys currently constitute the most advanced stage of karstification, with the development of the tributary drainages as the most recent stage. The structural directions show a NE-SW trend, represented by larger valleys, and subordinated to this, an NW-SE trend, where headwaters of low-order channels are located.